ETHICS EDUCATION AT THE UNIVERSITY: FROM TEACHING AN ETHICS MODULE TO EDUCATION FOR THE GOOD LIFE - de Reuyter, Doret; Schinkel, Anders (Bordón. Revista de Pedagogía, 2017)
INTRODUCTION. Due to professional crises both within and outside the university, ethics education is receiving increasing attention in both academic literature on higher education as well as in discussions in universities themselves. This article describes and evaluates four ways in which ethics could be part of the university curriculum: 1) teaching an academic ethics module, 2) introducing students into professional ethics; 3) promoting academic citizenship; 4) fostering the ability to live a good life. METHOD. The four interpretations of ethics education at the university are subjected to a philosophical analysis. In each case, the intention of the educator is scrutinized by means of a reflection on the interpretation of ‘ethics’ and ‘education’. For this relevant literature is used and philosophical argumentation applied. RESULTS. The results of the description and evaluation of each interpretation of ethics education are presented in each section. It is argued that the most minimal interpretation (teaching an ethics module) is less minimal than suggested yet insufficient. Teaching professional ethics is necessary, but will come to full fruition when students leave the university although their work ethics as students will add to their general professional ethical qualities. Dutch law requires universities to promote academic citizenship and personal development. This requires that students have the opportunity to obtain democratic civic dispositions and that universities provide frameworks with which students can form their conception of the good life. DISCUSSION. In the final section we supplement our conclusion that universities should promote academic citizenship and aim to foster students’ ability to live a good life with a sobering note and urgent call: successful pursuit of these aims is only possible in an ethical environment and ethos that are currently lacking in universities. Thus, universities also have to work on their own ethical standards.